Assessment of uncertainty in the CFD simulation of the wave-induced loads on a vertical cylinder. (November 2021) - Islam, Hafizul; Guedes Soares, C.
Abstract: The paper addresses different uncertainty analysis methods commonly used for uncertainty quantification in Computational Fluid Dynamics (CFD) studies and compares a constant Courant–Friedrichs–Lewy (CFL) number based approach for uncertainty estimation to the ITTC recommended grid and time-independent procedures. Four different uncertainty estimation procedures are presented and discussed. To compare their performance and better understand CFD related uncertainty quantification in wave load simulations on offshore structures, the methods are applied to a case study of the wave loads on a fixed vertical cylinder. The numerical or CFD wave tank is generated using the open-source CFD toolkit OpenFOAM. Uncertainty is assessed for the case study using four different uncertainty estimation procedures for verification and later, validation is attempted by comparing the CFD results with experiments. The study concludes that a constant CFL number based uncertainty study provides more stable results and is better suited for uncertainty estimation in CFD than the ITTC recommended individual grid and time step uncertainty study. Highlights: Four different procedures for uncertainty quantification in CFD are presented and discussed. To compare their performance they are applied to a case study of a fixed vertical cylinder facing incoming waves. The numerical or CFD wave tank is generated using the open-source CFD toolkit, OpenFOAM. The study concludes that each uncertainty analysis method has its pros and cons. A constant CFL number based study provides more stable results, compared to individual grid and time step uncertainty.